2008
DOI: 10.1038/onc.2008.144
|View full text |Cite
|
Sign up to set email alerts
|

Loss of responsiveness to IGF-I in cells with reduced cathepsin L expression levels

Abstract: The lysosomal cysteine proteinase cathepsin L is involved in proteolytic processing of internalized proteins. In transformed cells, where it is frequently overexpressed, its intracellular localization and functions can be altered. Previously, we reported that treatment of highly metastatic, murine carcinoma H-59 cells with small molecule cysteine proteinase inhibitors altered the responsiveness of the type I insulin-like growth factor (IGF-I) receptor and consequently reduced cell invasion and metastasis. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 58 publications
0
15
0
1
Order By: Relevance
“…CatL inhibition has been shown to be the cause of loss of responsiveness to IGF-I [40], which was associated with an increase in spontaneous apoptosis. CatL also degrades CatD [41], another lysosomal protease that mediates apoptosis [42].…”
Section: Discussionmentioning
confidence: 99%
“…CatL inhibition has been shown to be the cause of loss of responsiveness to IGF-I [40], which was associated with an increase in spontaneous apoptosis. CatL also degrades CatD [41], another lysosomal protease that mediates apoptosis [42].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Urbich et al showed that Ctsl is actually critical for the invasive capacity of endothelial progenitor cells, promoting neovascularization (Urbich et al , 2005). Intracellular Ctsl has been identified as a positive regulator of insulin-like growth factor 1 receptor signaling and of the experimental metastasis of tumor cells, which are dependent on insulin-like growth factor 1 receptor, and has also been found to have a role in promoting resistance toward chemotherapeutic drugs (Zheng et al , 2004; Navab et al , 2008). N-terminally truncated Ctsl has been found in the nucleus, in which it activates the CDP/Cux transcription factor, a positive regulator of the cell cycle involved in cellular transformation (Goulet et al , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant CTLA-2α selectively inhibits cathepsin L-like cysteine proteinases, papain-like proteases of animal tissues [13]. Cathepsin L affects the immune system [27, 28] but it is not clear if it is pro- or anti-apoptotic [2931]. We find that cAMP/PKA up-regulates cathepsin L activity but over-expression of CTLA-2α does not change its activity; thus, increased cathepsin L activity does not explain cAMP/PKA-promoted apoptosis in S49 cells.…”
Section: Discussionmentioning
confidence: 99%